Stomatal, Proline, and Leaf Water Status Characters of Some Cocoa Clones (Theobroma cacao L.) on Prolonged Dry Season - Fakhrusy Zakariyya; Bayu Setyawan; Agung Wahyu Susilo (Indonesian Coffee and Cocoa Research Institute, 2017)
ENSO (El Nino Southern Oscillation) occurring in 2015 in Indonesia caused drought stress and the decrease in the percentage of production and even death of plants. One effective and relatively inexpensive way of reducing damage and economic losses due to drought is the availibility of tolerant cocoa. The objective of this research was to obtain tolerant clones based on morpho-physiological characters under drought stress. The experiment was conducted in Kaliwining Experimental Station of Indonesian Coffee and Cocoa Research Institute (ICCRI) during dry season (El Nino period with 5 consecutive dry months, from May to October 2015). Stomata, proline, leaf water status was measured at the peak of dry season on tested cocoa clones. The cocoa clones that predicted tolerant against to drought stress were KW 641, KW 514, KW 535, KW 619, and KW 516, whereas the cocoa clones that predicted susceptible under drought stress were KW 609, KW 614, KW 635, KW 606, and KW 651. The treatment clones had higher values of RWC, leaf proline content, narrower width and length of stomata openings, but smaller value of WSD compared to susceptible clones. Meanwhile, the character of leaf thickness might not significanly different to the character of drought tolerance.